Amauronematus Konow, 1890 - Ökologie und Taxonomie der nordeuropäischen Arten des fallax-Komplexes (Hymenoptera, Tenthredinidae). - Schmidt, Stefan (Contributions to Entomology = Beiträge zur Entomologie, 1997)
Northern European sawflies in the Amauronematus fallax species complex were investigated taxonomically and ecologically. Extensive field collections were made in Northern Fennoscandia and host-associated larval material was reared to correlate larval forms with identifiable adult material. The ecological work centered on host plant relationships and host specificity. The complex contains 16 species in Northern Europe. Eleven of these are redescribed (Amauronematus amicula, A. arvii Saar., A. fallax Serv., A. hartigi Saar., A. histrio Serv., A. nuorbinjargi Saar., A. propinquus Saar., A. rufus Knw., A. schlueteri Ensl., A. septentrionalis Saar., A. subnitens Saar.) and 5 are described as new (Amauronematus betulae sp. n., A. mimus sp. n., A. nigrinus sp. n., A. subfuscus sp. n., A. tenuis sp. n.). Nematus stenogaster Förster, 1854, syn. nov. und Amauronematus festivus Saarinen, 1950, syn. nov. are regarded as synonyms of A. fallax. Previously used taxonomical characters were evaluated, and new morphological characters are introduced to characterize and identify species. They include the shape of the lancet (valvula 1) and the sawsheath (valvula 3) as well as the colouration of the sawsheath. A key is given to the females of all Northern European species of the complex. A discriminant analysis was conducted on three highly similar species of the complex. By including 17 characters it was possible to classify almost 98% of the specimens correctly (n=92). The number of characters could be reduced from 17 to 11 without increasing the rate of misclassification. - Rearing of field-collected larvae shoued that the Northern European species of the Amauronematus fallax complex are highly host specific. Laboratory experiments on oviposition behaviour of six species confirmed this conclusion and partly explained their host specificity. Sawfly species living on smooth-leaved willows showed a stronger oviposition preference than females from rough-leaved willows. In only one of the six species investigated experimentally the phenolic glycoside content in leaves may explain the observed oviposition preference. - The host specifity of the larvae of three species was studied. Larvae of species whose females showed a strong host preference when ovipositing showed a strong feeding preference for their usual host. In A. septentrionalis there was a negative correlation between feeding behaviour and the foliar phenolic glycoside content. To investigate the physiological specialization of larvae, no-choice feeding experiments were conducted. There was no difference in relative growth rate between groups, even though the usual host was included. Hence larvae seemed to be less specialized than would have been expected in view of their feeding preference. - The evolution of host specifity and species richness of sawflies on willows in Northern Fennoscandia are discussed. Keywords Northern Europe, Amauronematus, Salix, phytophagous insects, revision, life history, larvae, host plant specifity, discriminant analysis, preference experiment, speciation. Nomenclatural Acts analis Konow, 1897 (Amauronematus), Lectotype now a synonym of Amauronematus fallax (Serville, 1823) betulae Schmidt, 1997 (Amauronematus), spec. n. festivus Saarinen, 1950 (Amauronematus), syn. n. of Amauronematus fallax (Serville, 1823) mimus Schmidt, 1997 (Amauronematus), spec. n. nigrinus Schmidt, 1997 (Amauronematus), spec. n. schlueteri Enslin, 1915 (Amauronematus), Lectotype subfuscus Schmidt, 1997 (Amauronematus), spec. n. tenuis Schmidt, 1997 (Amauronematus), spec. n. rufescens Hartig, 1837 (Nematus), Lectotype now a synonym of of Amauronematus histrio (Serville, 1823) stenogaster Förster, 1854 (Nematus), syn. n. of Amauronematus fallax (Serville, 1823) taiganus Zhelochovtsev, 1988 (Nematus (Amauronematus)), syn. n. of Amauronematus septentrionalis Saarinen, 1950